Knowledge, attitude and practice of antibiotic prescribing among doctors working at Emergency Department Hospital Universiti Sains Malaysia - Omar, Nik Anis Ezdiani Raja (2016)
Introduction Antibiotic is the medication frequently prescribed among doctors at Emergency Department. Currently upsurge of antibiotic resistance has become a global concern. Imprudent use of antibiotics is a fundamental factor for an upsurge in the prevalence of antibiotic resistance. It is important to assess knowledge, attitude and practice of antibiotic prescribing among doctors at emergency department to improve better antibiotic prescribing behaviour. Objectives For general objective to evaluate knowledge, attitude and practice of antibiotic prescribing among doctors at emergency department Hospital Universiti Sains Malaysia. For specific objectives to determine the level of knowledge, attitude and practice of antibiotic prescribing among doctors at emergency departmentHospital Universiti Sains Malaysia and to compare means score of knowledge among difference designation. Methodology This is a cross sectional study to assess knowledge, attitude and practice of antibiotic among doctors at emergency department Hospital Universiti Sains Malaysia. This study was done from February 2015 to April 2015 including all doctors who agreed to involve in this study. Self administrated questionnaire was distributed to all doctors who agreed for involved in this study. Only completed questionnaires were analyzed and incomplete questionnaire were excluded from this study Results Respond were received from 81 respondents (83.3%) response rate. Mean knowledge score was 5.70 + 1.23. For comparison of knowledge score in between designation there was no significant different with F-stat (df) = 1.76 p = 0.179.Majority of respondents 69.1% (n = 56) strongly agree antibiotic resistance is worldwide problem, 24.7% (n = 20) strongly agree antibiotic is a national problem,only 3.7% (n = 3) strongly agree antibiotic resistance is problem in their practice.61.7% (n = 50) respondents were confident of their knowledge on antibiotics. 58% (n = 47) prescribe antibiotic more than once daily and most of respondents 93.8% (n =76) prescribe antibiotic to both in and outpatient. Conclusion This study revealed that knowledge score of our respondent is moderate, there was no significant difference of knowledge in between designation. Respondents aware that antibiotic resistance is worldwide and national problem but only small proportion realized that it’s problem in daily practice. Our respondent confident regarding knowledge of antibiotic and frequently prescribed antibiotic to patient.